(x^2+6x)^2-4(x+3)^2=156 с объяснением если можно
заранее

anna26102015 anna26102015    1   17.06.2020 13:20    5

Ответы
SakhanovMadiar1 SakhanovMadiar1  15.10.2020 14:16

-8  ;  2

Пошаговое объяснение:

(x^2+6x)^2-4(x+3)^2=156

(x²+6x)²-4(x+3)²=156

(x²+6x)²-4(x²+6x+9)=156

Пусть x²+6x = t  ⇒

t²-4(t+9)=156

t²-4t-36=156

t²-4t-36-156=0

t²-4t-192=0

D=16+768= 784

√784= 28

t=(4±28)/2

t= 16 ; -12

Обратная замена:

x²+6x=16

x²+6x-16=0

D=36+64=100

√100=10

x=(-6±10)/2= 2;-8

x²+6x=-12

x²+6x+12=0

D=36-48=-12

D=-12

Так как D<0 , то данное уравнение корней не имеет!

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика